The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31073/agrovisnyk202004-09
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plant density and doses of fertilizers on photosynthetic activity and yield of soybean of middle-ripening variety Sviatohor in conditions of irrigation

Abstract: Goal. To establish the optimal parameters of photosynthetic activity of crops of mid-season soybean variety Sviatogor in conditions of irrigation in the South of Ukraine depending on plant density and doses of nitrogen fertilizers. Methods. The field -for determination of yield; calculation -for optimization of doses of mineral fertilizers, plant density; measurement-weighе -for fixation of plant height, leaf area, and photosynthetic indices. Results. The density of sowing significantly influenced the leaf are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Галузеві підприємства хімічної промисловості України тривалий час зовсім не виробляли комплексні мікродобрива, однак ринок агрохімікатів мав пропозицію численних закордонних виробників [12,18]. Для зменшення імпорту поступово відбувалося формування масового серійного виробництва мікродобрив на підприємствах вітчизняної економіки [4,16]. За спектром дії та складом ці добрива різноманітні, оскільки містять практично всі мікроелементи [3,15].…”
Section: вступunclassified
“…Галузеві підприємства хімічної промисловості України тривалий час зовсім не виробляли комплексні мікродобрива, однак ринок агрохімікатів мав пропозицію численних закордонних виробників [12,18]. Для зменшення імпорту поступово відбувалося формування масового серійного виробництва мікродобрив на підприємствах вітчизняної економіки [4,16]. За спектром дії та складом ці добрива різноманітні, оскільки містять практично всі мікроелементи [3,15].…”
Section: вступunclassified
“…The compacted crops with two fertilisations with nitrogen and phosphorus fertilisers ensured the formation of grain with high protein and fat content. R. Vozhehova et al (2020), at the Institute of Irrigated Agriculture of the National Academy of Agrarian Sciences of Ukraine, studied the effect of plant density on grain yield of the mid-season soybean variety Svyatogor during 2016-2018. The highest yield level was provided by a sowing density of 600 thousand plants/ ha -4.32-4.47 t/ha in variants with fertilisation.…”
Section: Figure 6 Correlation-regression Model Of the Relationship Be...mentioning
confidence: 99%
“…This is confirmed by Carciochi et al (2019), who found changes in morphological parameters, an increase in the number of nodes and shorter internodes. Vozhehova et al (2020) observed the effect of increasing the thickening of crops from 600 to 800 thous. plants/ha on improving the photosynthetic potential, but already 900 thous.…”
Section: Source: Calculated By the Authors Using The Program Agrostatmentioning
confidence: 99%